Sinergitas Islam dan Budaya dalam Kearifan Lokal:: (Studi Kasus pada Komplek Pemakaman Raja-Raja Imogiri di Desa Panjaitan Imogiri) - Syarifah, Syarifah; Wahyudi, Wahyudi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2016)
Indonesia is a country that has assured a diversity of right to its citizens to confess a different religion as an individual faith. All the rules and orders of religion must be independently believed and obeyed by each adherent. They should openhandedly carry out both rituals as well as compulsions. Historically, Indonesia consists of diverse cultures that serves as local wisdoms which are inherent with society development in nature. Then, as one of among religions in Indonesia, Islam has been able to make local wisdoms as a means of propaganda for the success of spreading Islamic messages. This indicates that there is a sturdy synergy between local wisdoms and religious rituals in achieving their own goals. Moreover, in real practice, these two local wisdoms and religious rituals are habitually combined as the expressions of a civilized society, as done by the villagers of Panjaitan Imogiri located inside the cemetery of the Kings Imogiri. The King conducted Nguras Kong and Ngaras Siwur ceremonials surrounding the communities of local residents and they were confidently considered to be sacred rituals for blessing their lives. To conclude, the harmonization between both Islam and cultural diversity, Indonesia has been able to develop varied local wisdoms to open a wide range of individual freedom for respecting the different beliefs and traditions among the society members for common peace and prosperity.